Diversity management in East Asian universities: focusing on the inclusion of international students/faculty and gender equality in Japanese universities - Kunimitsu Mamiya (Journal of Contemporary East Asia Studies)
This paper discusses the current status and challenges of diversity and inclusion in East Asian universities, particularly in Japan. Diversity has primarily been examined in the field of business administration and has been actively debated in the United States, where a diverse society exists. This paper explores diversity in the context of higher education, primarily in East Asian universities.The Sustainable Development Goals include goals such as “(inclusive and equitable) quality education” and “gender equality,” and the promotion of diversity and inclusion is recognized as an important issue from the perspective of global sustainable development. I summarize the effects and importance of diversity based on previous studies and analyze the current status and challenges by reviewing university statistics in various countries. In conclusion, the degree of progress in diversity in East Asian universities is still limited compared to universities in Europe and the U.S. Additionally, the status of diversity initiatives in East Asian universities is not uniform, and Japanese universities are relatively behind. However, there is a long-term trend toward steady improvement in diversity promotion at Japanese universities.On the other hand, inclusion – making the most of diversity – remains a challenge for further development of domestic diversity.